Sintered ferrite magnets and rotating electrical machines
Patent Information
- Application Number
- JP2020060500
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-30
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-03-30
Smart Images

Figure 0007636106000001 
Figure 0007636106000002 
Figure 0007636106000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sintered ferrite magnet and a rotating electric machine. [Background technology]
[0002] It is known that in order to obtain a sintered ferrite magnet having excellent magnetic properties (high residual magnetic flux density Br, high coercive force Hcj), Sr ferrite, which is a hexagonal M-type ferrite and contains at least Sr, is used.
[0003] Patent Document 1 discloses Sr ferrite that contains at least La as a rare earth element and in which part of the Fe is replaced with Co. By using Sr ferrite that contains La and Co as essential elements, a sintered ferrite magnet with high Br and high Hcj can be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3337990 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to obtain a sintered ferrite magnet having high Br and high Hcj in a composition with a small Co amount. [Means for solving the problem]
[0006] In order to achieve the above object, the sintered ferrite magnet according to the present invention comprises: Contains A, R, Fe and Co, 1-x R x (Fe 12-y Co y ) z O 19(atomic ratio) of the sintered ferrite magnet having hexagonal M-type ferrite, A is one or more selected from Sr, Ba, and Pb; R is one or more rare earth elements selected, R includes at least La; 0.13≦x≦0.23 10.80≦(12-y)z≦12.10 0.13≦yz≦0.20 Meet the following.
[0007] When Ca contained in the sintered ferrite magnet is converted into oxide, the CaO content is defined as Mc (mass%), The relationship 0.30≦Mc≦0.85 may be satisfied.
[0008] When the Si contained in the sintered ferrite magnet is converted into an oxide, the SiO content is defined as Ms (mass%), The range may be 0.35≦Ms≦0.60.
[0009] When Ba contained in the sintered ferrite magnet is converted into oxide, the content of BaO is defined as Mb (mass%), The range may be 0≦Mb≦0.15.
[0010] When the Al contained in the sintered ferrite magnet is converted into an oxide, the content of Al2O3 is defined as Ma (mass%), The range may be 0≦Ma≦0.90.
[0011] When the Cr contained in the sintered ferrite magnet is converted into an oxide, the Cr2O3 content is defined as Mr (mass%), The relationship 0≦Mr≦0.10 may be satisfied.
[0012] A rotating electrical machine according to the present invention contains the above-mentioned sintered ferrite magnet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the present invention will be described based on an embodiment.
[0014] The sintered ferrite magnet according to the present embodiment contains A, R, Fe and Co. 1-x R x (Fe 12-y Co y ) z O 19 The sintered ferrite magnet has a hexagonal M-type ferrite that can be expressed as (atomic ratio). In this specification, the sintered ferrite magnet according to this embodiment may be referred to as a sintered ferrite magnet. A is one or more elements selected from strontium (Sr), barium (Ba) and lead (Pb). R is one or more elements selected from rare earth elements, including at least lanthanum (La), and x, (12-y)z and yz satisfy the following formula. 0.13≦x≦0.23 10.80≦(12-y)z≦12.10 0.13≦yz≦0.20
[0015] Sintered ferrite magnets are A 1-x R x (Fe 12-y Co y ) z O 19 It has hexagonal M-type (hexagonal magnetoplumbite-type) ferrite, which can be expressed as (atomic ratio).
[0016] Specifically, sintered ferrite magnets are 1-x R x (Fe 12-y Co y ) z O 19 (atomic ratio). The ferrite particles are crystalline particles and have a hexagonal magnetoplumbite type crystal structure. The fact that the ferrite particles have a hexagonal magnetoplumbite type crystal structure can be confirmed by, for example, X-ray structural diffraction.
[0017] Sintered ferrite magnets have a low cobalt (Co) content (yz). Because sintered ferrite magnets have little excess Co, the formation of different phases is suppressed and a uniform microstructure is formed. This gives sintered ferrite magnets a high Br and high Hcj. Furthermore, because sintered ferrite magnets have a low Co content (yz), they can be produced at low cost.
[0018] A is one or more selected from Sr, Ba, and Pb. The content of Sr in A may be 90 at % or more, or A may be only Sr. The content of Ba in A may be 1 at % or less.
[0019] R is one or more elements selected from rare earth elements, and includes at least La as R. The content ratio of La in R may be 90 at % or more, or R may be La only.
[0020] The sintered ferrite magnet may satisfy the following formula: 0.14≦x≦0.23 11.60≦(12-y)z≦12.10 0.13≦yz≦0.19
[0021] When x, (12-y)z, and yz satisfy these formulas, Br and Hcj tend to be further improved.
[0022] If x is too small, Br decreases. If x is too large, Hcj decreases. Furthermore, if 0.14≦x≦0.23 is satisfied, manufacturing stability is likely to be improved. Manufacturing stability refers to the property that the change in magnetic properties (especially Hcj) is small even if the firing temperature changes.
[0023] If (12-y)z is too small, Hcj decreases. If (12-y)z is too large, Br and / or Hcj decrease. Also, if 11.60≦(12-y)z≦12.10 is satisfied, manufacturing stability is likely to be improved.
[0024] If yz is too small, Hcj decreases. If yz is too large, Br decreases and the cost increases. Also, if yz satisfies 0.13≦yz≦0.19, manufacturing stability is likely to improve.
[0025] The sintered ferrite magnet may contain calcium (Ca). When the Ca contained in the sintered ferrite magnet is converted into oxide, the CaO content is Mc (mass%), The relationship may be satisfied as 0.30≦Mc≦0.85, or as 0.33≦Mc≦0.78.
[0026] The lower the CaO content, the lower the Br tends to be. The higher the CaO content, the lower the Hcj tends to be. In addition, when 0.33≦Mc≦0.78 is satisfied, the manufacturing stability is likely to be improved.
[0027] The sintered ferrite magnet may contain silicon (Si). When the Si contained in the sintered ferrite magnet is converted into an oxide, the SiO2 content is expressed as Ms (mass%), and The range may be 0.35≦Ms≦0.60, or 0.45≦Ms≦0.60.
[0028] The lower the SiO2 content, the lower the Hcj tends to be. The higher the SiO2 content, the lower the Br tends to be. In addition, when 0.45≦Ms≦0.60 is satisfied, the manufacturing stability is likely to be improved.
[0029] The sintered ferrite magnet may contain Ba. When Ba contained in the sintered ferrite magnet is converted into oxide, the content of BaO is defined as Mb (mass%), and The range may be 0≦Mb≦0.15, may be 0.03≦Mb≦0.15, or may be 0.08≦Mb≦0.15.
[0030] If the BaO content is too high, Br is likely to decrease, while if 0.08≦Mb≦0.15 is satisfied, production stability is likely to improve.
[0031] In addition, Ba is A 1-x R x (Fe 12-y Co y ) z O 19 may be contained in the sintered ferrite magnet as A, 1-x R x (Fe 12-y Co y ) z O 19 The sintered ferrite magnet may contain other Ba compounds or Ba alone.
[0032] The sintered ferrite magnet may contain aluminum (Al). When the Al contained in the sintered ferrite magnet is converted into an oxide, the content of Al2O3 is defined as Ma (mass%), and The range may be 0≦Ma≦0.90, or 0.05≦Ma≦0.90.
[0033] If the content of Al2O3 is too high, Br tends to decrease.
[0034] The sintered ferrite magnet may contain chromium (Cr). When the Cr contained in the sintered ferrite magnet is converted into an oxide, the content of Cr2O3 is defined as Mr (mass%), and The range may be 0≦Mr≦0.10, or 0.05≦Mr≦0.10.
[0035] If the Cr2O3 content is too high, Br tends to decrease.
[0036] The sintered ferrite magnet may contain manganese (Mn), magnesium (Mg), copper (Cu), nickel (Ni) and / or zinc (Zn) as impurities. There are no particular limitations on the amount of these impurities, but these impurities may be contained in an amount of 0.5% by mass or less, with the entire sintered ferrite magnet being 100% by mass. Furthermore, these impurities may be contained in a total amount of 0.7% by mass or less.
[0037] The sintered ferrite magnet may further contain elements other than the above elements, specifically elements other than A, R, Fe, Co, oxygen (O), Ca, Si, Al, Cr, Mn, Mg, Cu, Ni, and Zn, as unavoidable impurities. The unavoidable impurities may be contained in a total amount of 3 mass% or less, with the entire sintered ferrite magnet being 100 mass%.
[0038] The method of calculating Mc will be described below. Note that the methods of calculating Ms, Mb, Ma, and Mr are also the same.
[0039] First, the content of Ca contained in the sintered ferrite magnet is measured by a method commonly used in the technical field. Then, the content of Ca is converted to oxide (CaO). The contents of the above elements other than O contained in the sintered ferrite magnet, specifically A, R, Fe, Co, Ca, Si, Ba, Al, Cr, Mn, Mg, Cu, Ni, and Zn, are also measured in the same manner and converted to oxides. Specifically, they are converted to AO, R2O3, Fe2O3, Co3O4, CaO, SiO2, BaO, Al2O3, Cr2O3, MnO, MgO, CuO, NiO, and ZnO. Furthermore, the contents of unavoidable impurities are also measured in the same manner and converted to oxides as appropriate.
[0040] Then, Mc can be calculated by dividing the CaO content by the total content of all the above oxides.
[0041] There is no particular limitation on the density of the sintered ferrite magnet. For example, the density measured by the Archimedes method is 4.9 g / cm 3 More than 5.2g / cm 3 The density may be within the above range, in particular 5.0 g / cm 3 By satisfying the above, Br tends to be good.
[0042] The method for producing the sintered ferrite magnet according to this embodiment will be described below.
[0043] In the following embodiment, an example of a method for producing a sintered ferrite magnet is shown. In this embodiment, the sintered ferrite magnet can be produced through a blending step, a calcining step, a pulverizing step, a molding step, and a sintering step. Each step is described below.
[0044] <Blending process> In the blending step, the raw materials of the ferrite sintered magnet are blended to obtain a raw material mixture. The raw materials of the ferrite sintered magnet include compounds (raw material compounds) that contain one or more of the elements that constitute the raw materials. The raw material compounds are preferably in powder form, for example.
[0045] Examples of the raw material compounds include oxides of each element, or compounds that become oxides by firing (carbonates, hydroxides, nitrates, etc.). Examples include SrCO3, BaCO3, PbCO3, La2O3, Fe2O3, Co3O4, CaCO3, SiO2, MgO, Al2O3, Cr2O3, MnO, MgO, NiO, CuO, and ZnO. The average particle size of the powder of the raw material compounds may be about 0.1 μm to 2.0 μm.
[0046] For example, the raw materials are weighed so as to obtain the desired composition of the ferrite magnetic material. Then, the raw materials are mixed and pulverized for about 0.1 to 20 hours using a wet attritor, ball mill, etc. In this mixing process, it is not necessary to mix all the raw materials, and some of them may be added after calcination, which will be described later.
[0047] <Pre-firing process> In the calcination step, the raw material mixture obtained in the blending step is calcined. Calcination can be carried out, for example, in an oxidizing atmosphere such as air. The calcination temperature is preferably in the range of 1100°C to 1300°C. The calcination time can be 1 second to 10 hours.
[0048] The primary particle size of the calcined body obtained by calcination may be 10 μm or less.
[0049] <Crushing process> In the pulverization step, the calcined body that has become granular or lumpy in the calcination step is pulverized into powder. This facilitates shaping in the shaping step described below. In the pulverization step, as described above, raw materials that were not mixed in the mixing step may be added (post-addition of raw materials). The pulverization step may be performed in two stages, for example, by pulverizing the calcined body into coarse powder (coarse pulverization) and then pulverizing the powder further into fine powder (fine pulverization).
[0050] Coarse pulverization is carried out, for example, using a vibration mill or the like until the average particle size becomes 0.5 μm to 10.0 μm. In fine pulverization, the coarsely pulverized material obtained by coarse pulverization is further pulverized by a wet attritor, ball mill, jet mill, or the like.
[0051] In the fine pulverization, the average particle size of the obtained finely pulverized material is preferably about 0.08 μm to 1.00 μm. The specific surface area of the finely pulverized material (measured, for example, by the BET method) is 4 m 2 / g~12m 2 The pulverization time varies depending on the pulverization method, and for example, in the case of a wet attritor, it can be about 30 minutes to 20 hours, and in the case of wet pulverization using a ball mill, it can be about 1 hour to 50 hours.
[0052] In the fine pulverization step, in the case of a wet method, in addition to an aqueous solvent such as water, a non-aqueous solvent such as toluene or xylene can be used as a dispersion medium. The use of a non-aqueous solvent tends to provide high orientation during wet molding, which will be described later. On the other hand, the use of an aqueous solvent such as water is advantageous from the viewpoint of productivity.
[0053] In the fine pulverization step, for example, known polyhydric alcohols or dispersants may be added to increase the degree of orientation of the sintered body obtained after firing.
[0054] <Forming and sintering process> In the molding and sintering process, the pulverized material (preferably finely pulverized material) obtained after the pulverization process is molded to obtain a molded body, which is then sintered to obtain a sintered body. The molding can be performed by any of the methods of dry molding, wet molding, and Ceramic Injection Molding (CIM).
[0055] In the dry molding method, for example, a magnetic field is applied while the dried magnetic powder is pressure molded to form a molded body, and then the molded body is sintered. In general, the dry molding method has the advantage that the time required for the molding process is short because the dried magnetic powder is pressure molded in a mold.
[0056] In the wet compaction method, for example, a slurry containing magnetic powder is pressure-molded in an applied magnetic field while removing the liquid component to form a compact, and then the compact is sintered. The wet compaction method has the advantage that the magnetic powder is easily oriented by the magnetic field during molding, and the magnetic properties of the sintered magnet are good.
[0057] In addition, the molding method using CIM involves heating and kneading dried magnetic powder together with a binder resin, forming a pellet that is then injection molded in a mold to which a magnetic field is applied to obtain a preform, which is then de-bindered and then fired.
[0058] The wet molding will be described in detail below.
[0059] (Wet molding and firing) When a sintered ferrite magnet is obtained by a wet compaction method, the above-mentioned fine pulverization step is performed in a wet manner to obtain a slurry. This slurry is then concentrated to a predetermined concentration to obtain a slurry for wet compaction. This can be used for compaction.
[0060] The slurry can be concentrated by centrifugation, a filter press, etc. The content of the fine pulverizing agent in the wet compacting slurry can be about 30% by mass to 80% by mass based on the total amount of the wet compacting slurry.
[0061] In the slurry, water can be used as a dispersion medium for dispersing the finely pulverized material. In this case, a surfactant such as gluconic acid, gluconate, or sorbitol can be added to the slurry. A non-aqueous solvent can also be used as the dispersion medium. An organic solvent such as toluene or xylene can be used as the non-aqueous solvent. In this case, a surfactant such as oleic acid can be added.
[0062] The wet compacting slurry may be prepared by adding a dispersion medium and the like to the finely pulverized material in a dry state after the fine pulverization.
[0063] In the wet compaction, the slurry for wet compaction is then compacted in a magnetic field. In this case, the compaction pressure is 9.8 MPa to 98 MPa (0.1 ton / cm 2 ~1.0ton / cm 2 The applied magnetic field can be about 400 kA / m to 1600 kA / m. The pressure application direction during molding and the magnetic field application direction may be the same or perpendicular to each other.
[0064] The green body obtained by wet molding can be sintered in an oxidizing atmosphere such as air. The sintering temperature can be 1050°C to 1270°C. The sintering time (the time to hold at the sintering temperature) can be about 0.5 hours to 3 hours. Then, a ferrite sintered magnet is obtained by sintering.
[0065] When obtaining a green body by wet molding, it is possible to heat the green body from room temperature to about 100°C at a temperature increase rate of about 2.5°C / min before reaching the firing temperature. By thoroughly drying the green body, it is possible to prevent cracks from occurring.
[0066] Furthermore, when a surfactant (dispersant) or the like is added, it is possible to sufficiently remove it (degreasing treatment) by heating at a temperature increase rate of about 2.0°C / min in a temperature range of about 100°C to 500°C. Note that these treatments may be carried out at the beginning of the firing process, or may be carried out separately before the firing process.
[0067] A preferred method for producing a sintered ferrite magnet has been described above, but the production method is not limited to the above, and the production conditions, etc. can be changed as appropriate.
[0068] The shape of the sintered ferrite magnet of the present invention is not limited as long as it has the composition of the ferrite of the present invention. For example, the sintered ferrite magnet may be in the shape of an anisotropic arc segment, a flat plate, Cylindrical, cylindrical, etc. The sintered ferrite magnet of the present invention can have a high Br while maintaining a high Hcj, regardless of the shape of the magnet.
[0069] There is no particular limit to the use of the sintered ferrite magnet obtained by the present invention, but it can be used, for example, in a rotating electric machine. The rotating electric machine obtained by the present invention has the above-mentioned sintered ferrite magnet. There is no particular limit to the type of rotating electric machine. For example, motors and generators can be mentioned. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0071] <Blending process> As starting materials, SrCO3, La2O3, Fe2O3, Co3O4, CaCO3, SiO2, BaCO3, Al2O3 and Cr2O3 were prepared and weighed so that the final composition of the sintered ferrite magnet would be the composition of each sample listed in Tables 1 to 9.
[0072] Of the above starting materials, the materials other than La2O3 and Co3O4 were mixed and pulverized in a wet attritor to obtain a slurry-like raw material mixture.
[0073] <Pre-firing process> After drying this raw material mixture, it was subjected to a calcination treatment in air at 1200°C for 2 hours to obtain a calcined body.
[0074] <Crushing process> The calcined body was coarsely pulverized in a rod mill to obtain a coarsely pulverized material. Next, La2O3 and Co3O4 were added and finely pulverized in a wet ball mill for 28 hours to obtain a slurry. The obtained slurry was adjusted to a solid content of 70 to 75% by mass to obtain a slurry for wet compaction.
[0075] <Forming and sintering process> Next, a preform was obtained using a wet magnetic field molding machine. The molding pressure was 50 MPa, and the applied magnetic field was 800 kA / m. The pressure direction during molding and the magnetic field direction were set to be the same. The preform obtained by wet molding was disk-shaped, with a diameter of 30 mm and a height of 15 mm.
[0076] The preform was sintered in air at the optimum sintering temperature for one hour to obtain a sintered ferrite magnet.
[0077] A method for determining the optimum firing temperature in this embodiment will now be described.
[0078] First, for each composition of the experimental example, sintered bodies were produced by sintering at temperatures varying from 1190 to 1230°C in increments of 10°C. That is, a total of five sintered bodies were produced for each experimental example. Then, the density of each sintered body was measured, and the sintering temperature of the sintered body with the highest density was determined as the optimum sintering temperature. The density of the sintered body was measured by the Archimedes method.
[0079] Each sintered ferrite magnet was subjected to fluorescent X-ray quantitative analysis, and it was confirmed that each sintered ferrite magnet had the composition shown in Tables 1 to 9.
[0080] Furthermore, X-ray diffraction measurements confirmed that each of the sintered ferrite magnets in Tables 1 to 9 had a hexagonal M-type structure.
[0081] <Measurement of magnetic properties (Br, Hcj)> In each experimental example, the top and bottom surfaces of each sintered ferrite magnet obtained by sintering at the optimum sintering temperature were machined, and then the magnetic properties were measured using a BH tracer with a maximum applied magnetic field of 1989 kA / m in an air atmosphere at 25°C. The results are shown in Tables 1 to 9. In this example, the magnetic properties were considered to be good when Br was greater than 420.0 mT and Hcj was greater than 330.0 kA / m. The magnetic properties were considered to be even better when Br was greater than 435.0 mT and Hcj was greater than 345.0 kA / m.
[0082] <Cost column> In the cost column of this experimental example, regarding the content (yz) of Co, which is a high-cost raw material, if yz≦0.20, it was deemed acceptable, and if yz>0.20, it was deemed unacceptable.
[0083] [Table 1]
[0084] [Table 2]
[0085] [Table 3]
[0086] [Table 4]
[0087] [Table 5]
[0088] [Table 6]
[0089] [Table 7]
[0090] [Table 8]
[0091] [Table 9]
[0092] From Tables 1 to 9, in each Example in which x, (12-y)z, and yz are all within a specific range, Br and Hcj are good, and the cost is also excellent. In contrast, when any of x, (12-y)z, and yz is outside the specific range, Br, Hcj, and / or cost are deteriorated.
[0093] The results show that when CaO, SiO2, BaO, Al2O3 and / or Cr2O3 are contained within respective suitable ranges, the magnetic properties are likely to be further improved.
Claims
1. A, R, Fe and Co, 1-x R x (Fe 12-y Co y ) z O 19 (atomic ratio), A is one or more selected from Sr, Ba, and Pb; R is one or more elements selected from rare earth elements, R includes at least La; 0.13≦x≦0.23 10.80≦(12-y)z≦12.10 0.13≦yz≦0.19 Fulfilling When Ba contained in the sintered ferrite magnet is converted into oxide, the content of BaO is defined as Mb (mass%), A sintered ferrite magnet that satisfies 0.03≦Mb≦0.
15.
2. When the Ca contained in the sintered ferrite magnet is converted into an oxide, the CaO content is Mc (mass%), The sintered ferrite magnet according to claim 1, wherein 0.30≦Mc≦0.85 is satisfied.
3. When the Si contained in the sintered ferrite magnet is converted into an oxide, it is SiO 2 The content is Ms (mass%), The sintered ferrite magnet according to claim 1 or 2, which satisfies 0.35≦Ms≦0.
60.
4. When the Al contained in the sintered ferrite magnet is converted into an oxide, the Al 2 O 3 The content is Ma (mass%), The sintered ferrite magnet according to any one of claims 1 to 3, which satisfies 0≦Ma≦0.
90.
5. When the Cr contained in the sintered ferrite magnet is converted into an oxide, Cr 2 O 3 The content of is Mr (mass%), The sintered ferrite magnet according to any one of claims 1 to 4, which satisfies 0≦Mr≦0.
10.
6. A rotating electrical machine comprising the sintered ferrite magnet according to any one of claims 1 to 5.
Citation Information
Patent Citations
Permanent magnet and manufacturing method therefor
JP2002334803A
Oxide magnetic materials, ferrite particles, sintered magnets, bonded magnets, magnetic recording media and motors
JP3337990B2